PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN CANVA DAN WORDWALL PADA MATERI MAKANAN UNTUK PESERTA DIDIK KELAS VIII DI SMPN 2 PANGKAH - ., Sudiyanti; Munadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The availability of interactive learning media at SMPN 2 Pangkah is still lacking. This study aims to produce learning media products that are suitable and effective for use in the learning activities of students in grade VIII at SMPN 2 Pangkah. The research method used was research and development (R&D) with the ADDIE development model, but limited to the analysis, design, and development stages. The subjects used in this study were eighth-grade students at SMPN 2 Pangkah, with the product being tested on 30 students. Data collection techniques included interviews, observation, and questionnaires. The results of the development research showed that there was a need for interactive science learning media assisted by Canva and Wordwall, as determined through the analysis results. After completing the design and development stages, interactive science learning media assisted by Canva and Wordwall was produced, which was deemed very feasible by three media experts and subject matter experts, with an average final validation result of 94.45%. Based on the product trial results, the use of interactive science learning media assisted by Canva and Wordwall on food material proved to be effective in improving student learning outcomes, from an initial average learning outcome of 7.67 to 8.7.